83.6k views
5 votes
(2³)² solve this problem

User Fabia
by
5.9k points

2 Answers

4 votes

Answer:

Formula used : (a^m)^n = a^(m×n)

→ (2³)² = 2³*² = 2⁶ = 64

  • 64 is the right answer.
User Muni Chittem
by
4.9k points
3 votes

Answer:


(2^3)^2 = 64

Explanation:

Option 1:

Using the following rule:


(a^n)^m = a^(nm)

Put in our expression,

a = 2

n = 3

m = 2


(a^n)^m = a^(nm)


(2^3)^2 = 2^(3*2)=2^6=64

Option 2:

Using the following rule:


a^n * a^m = a^(n+m)

Since our expression is the same as multiplying 2³ with itself, we can write it as a multiplication.


(2^3)^2 = 2^3 * 2^3

If we compare this with
a^n * a^m, we can see that

a = 2

n = 3

m = 3 (in this case, n and m are equal)


a^n*a^m = a^(n+m)


2^3*2^3 = 2^(3+3) = 2^6 = 64

Answer:
(2^3)^2 = 64

User Cortes
by
5.1k points